Noise Pollution: A Public Wellbeing Challenge - Dr. Manju Dewan (Journal of Advanced Zoology, 2022)
Noise pollution is becoming a big challenge in daily life affecting the wellbeing of people and the quality of life. Excessive noise seriously harms human wellness and interferes with people’s daily activities at school, work, home and during leisure time. The objective of the study was to assess the impact of noise on human health. A total 515 individuals from different wayside Government Offices, Private Organizations and Commercial Business Centers on both sides of busy roads of the city were interviewed for attitudinal responses by using the questionnaire. A relationship was developed between different traffic noise parameters and its harmful impact on work competency and efficiency of individuals. Statistical analysis was also carried out between measured and predictive values of the percentage of highly annoyed group of individuals. The subjects claimed that there were children and senior citizens in their houses who were more prone to noise pollution and noise was affecting them badly and was changing their behaviour. The study indicated that the problems of Headache, Hypertension and Stress had been more severe as compared to the problem of Irritation and Insomnia and these were affecting more severely to persons having other health concerns. They were of the view that awareness and guidance to general public must be provided to safeguard the health related challenges.